Meta-Analytic Review on Third-Generation Biodiesel - de Almeida Moreira, Bruno Rafael; de Almeida Viana, Charlene Raquel; Cruz, Victor Hugo; Lopes, Paulo Renato Matos; da Silva Viana, Ronaldo; Ramos, Ricardo Alan Verdú (Bioenergy research, 2022)
Microalgal biodiesel is technically viable to power diesel engines. This third-generation biofuel has great performance of combustion and can reduce emission of greenhouse gases into the atmosphere. However, its production is currently very expensive, relative to petrochemical diesel. Development and implementation of strategies to optimize productivity and quality of biomass and thus ensure this future-proof biofuel is economically feasible to fabricate and competitive with diesel oil on an industrial scale is challenging. This meta-analytic overview documents the diversity of fastest-growing, oil-accumulating microalgae; performance of cultures and systems; strategies for inducing lipids; and quality and economics of microalgal biodiesel. The microalgae, Neochloris oleoabundans , Scenedesmus obliquus , Desmodesmus sp., and Micractinium sp., are hyperaccumulators of lipids. The genre, Micractinium sp., is a thermophile, and thus it can resist hydrothermal streams. Complementarily, it is the fastest to grow and the most productive in both biomass and biodiesel. This should be of great importance to roll-out sustainable, high-performance algal systems in marginal lands in tropical zones, where the heat often makes the planning and management of projects difficult and expensive. Heat shock, nutritional starvation, and photoperiod are the most effective algae-specific strategies for inducing mechanisms for lipogenesis in Ankistrodesmus dimorphus , Chlorella vulgaris and Leptolyngbya sp., Cylindrotheca closterium and N. oleoabundans , and Amphora subtropica and Dunaliella sp., respectively. Rhodococcus sp. produces a significant amount of biomass at very low cost, relative to diesel oil. The concept of synergistically co-culturing microalgae with this photosynthetically active bacterium may be an option to save the producer the expenditures and uncertainties of third-generation biodiesel.